Clinical outcomes of different patent ductus arteriosus treatment in preterm infants born between 28 and 32 weeks in Taiwan - Hao-Wei Chung; Shu-Ting Yang; Fu-Wen Liang; Hsiu-Lin Chen (Pediatrics and Neonatology)
Background: The patent ductus arteriosus (PDA) treatment in very preterm infants is controversial. This study focused on preterm infants born at 28–32 weeks of gestation and analyzed the association between various PDA treatments and clinical outcomes. Methods: We conducted a retrospective cohort study of infants born at 28–32 weeks of gestation between 2016 and 2019 at 22 hospitals in the Taiwan Premature Infant Follow-up Network. We categorized the infants into four groups according to treatment strategies: medication, primary surgery, medication plus surgery, or conservative treatment. Results: A total of 1244 infants presented with PDA, and 761 (61.1%) were treated. Medication was the predominant treatment (50.0%), followed by conservative treatment (38.9%), medication plus surgery (7.6%), and primary surgery (3.5%). The risk of mortality was not reduced in the active treatment group compared to the conservative treatment group. There was a higher prevalence of severe intraventricular hemorrhage, necrotizing enterocolitis (NEC), and any degree of bronchopulmonary dysplasia (BPD) in both the primary surgery and medication plus surgery groups than in the conservative treatment group. After adjustment, both the primary surgery and medication plus surgery groups still had higher odds ratios for the occurrence of NEC and any degree of BPD. Conclusions: Compared with active PDA treatment, conservative treatment for PDA did not increase the risk of mortality and morbidity in very preterm infants born at 28–32 weeks of gestation. The risks and benefits of surgery (PDA ligation) in these infants must be considered cautiously.